Comparison between laser and TIG welding of electron beam melted Ti6Al4V parts - ŞEN, MURAT; KURT, MUSTAFA (My University, 2023)
A large number of metal parts specific to the aviation, energy, and biomedical industries are produced by the electron beam melting (EBM) method, which is one of the powder bed additive manufacturing techniques. The limited build volume of EBM machines does not allow the production of parts in the desired dimensions. One way to overcome this limitation is to weld small size additive manufactured parts. In this study, EBMed Ti6Al4V tensile specimens were joined by laser (LBW) and tungsten inert gas (TIG) welding. Welding morphologies, microstructures, and mechanical properties of joints were investigated. The main defects in the samples are pore formation and insufficient penetration. The weld zones of TIG samples contain a higher amount of pores than laser samples, and these pores are distributed over the entire area of the weld. The pores are less than 200 » μm in diameter. TIG welded samples exhibited higher mechanical properties than laser welded samples. The highest microhardness was measured in the weld zone. Microhardness of laser welded samples are higher than TIG welded samples. While the welding regions of TIG welded samples consist of coarse and acicular α and α + β structures, laser welded samples consist of thin and acicular α′ structure.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; Makine Mühendisliği; General Materials Science; Physical Sciences; Mechanics of Materials; Mechanical Engineering; electron beam melting (EBM); laser beam welding (LBW); mechanical properties; Ti-6Al-4V alloy; tungsten inert gas welding (TIG)